The clinical presentation of attention deficit‐hyperactivity disorder (ADHD) in children with 22q11.2 deletion syndrome. Issue 8 (24th September 2015) - Niarchou, Maria; Martin, Joanna; Thapar, Anita; Owen, Michael J.; van den Bree, Marianne B. M.
Abstract : Background: Although attention deficit‐hyperactivity disorder (ADHD) is the most prevalent psychiatric disorder in children with 22q11.2DS, it remains unclear whether its clinical presentation is similar to that in children with idiopathic ADHD. The aim of this study is to compare the ADHD phenotype in children with and without 22q11.2DS by examining ADHD symptom scores, patterns of psychiatric comorbidity, IQ and gender distribution. Methods: Forty‐four children with 22q11.2DS and ADHD (mean age = 9.6), 600 clinic children (mean age = 10.8) and 77 children with ADHD from a population cohort (mean age = 10.8) participated in the study. Psychopathology was assessed using parent‐report research diagnostic instruments. Results: There was a higher proportion of females in the 22q11.2DS ADHD sample in relation to the clinical sample (χ 2  = 18.2, P  < 0.001). The 22q11.2DS group showed a higher rate of ADHD inattentive subtype (χ 2  = 114.76, P  < 0.001), and fewer hyperactive‐impulsive symptoms compared to the clinical group (z = 8.43, P  < 0.001). The 22q11.2DS ADHD group parents reported fewer oppositional defiant disorder/conduct disorder symptoms (z = 6.33, P  < 0.001) and a higher rate of generalized anxiety disorder (χ 2  = 4.56, P  = 0.03) in relation to the clinical group. Two percent of the 22q11.2 DS ADHD sample had received ADHD treatment. The results were similar when the 22q11.2 ADHD group was compared to the population cohort ADHD group. Conclusions: The clinical presentation of ADHD and patterns of co‐morbidity in 22q11.2DS is different from that in idiopathic ADHD. This could lead to clinical under‐recognition of ADHD in this group. Examining psychopathology in 22q11.2DS can provide insights into the genetic origins of psychiatric problems with implications beyond the 22q11.2DS population. © 2015 Wiley Periodicals, Inc.